Perancangan Interior Pusat Fotografi di Surabaya - Kurniadji, Rachmad (Intra, 2013)
Looking at the facts in Surabaya that photography was a much-loved activity, but there is still no place that can hold the required facilities. Also still a little place to appreciate the photography works, so photography was limited as only activity, but how photography works shown to public is still not enough.Of most people today prefer to something instantly, this interior design goal is to provide a place for public, especially photographers, by providing the necessary facilities for photographic activity. By carrying out a concept of âone-stop serviceâ, so as to facilitate the visitors.